Analysis of Public Health Centre Financing using the District Health Account (DHA) Model in Karangasem District, Bali, Indonesia - Liena Sofiana; Gunadi Ardana; Suci Musvita Ayu (Public Health and Preventive Medicine Archive, 2020)
Background and purpose: Nosocomial infections can cause a significant number of deaths every day worldwide. Failure to perform good and proper hand hygiene is considered a major cause of infections related to health care. Health workers who are the most vulnerable in transmitting infections are nurses, because they are accompanying patients for 24 hours. This study aims to explore the relationship between knowledge, attitudes and motivation with the level of nurses’ compliance in hand hygiene practices in Class III inpatient wards of Pembina Kesejahteraan Umat (PKU) Muhammadiyah Hospital, Gamping, Yogyakarta. Methods: This was a cross-sectional observational analytic study. The study involved all 41 nurses working in Class III inpatient wards at PKU Muhammadiyah Gamping Hospital. The instruments for data collection was a questionnaire and an observation sheet. Data was analysed with statistical software comprised of univariate and bivariate analysis with Chi-square test and Fisher’s Exact test. Results: The results indicate the prevalence of nurses’ hand hygiene compliance was 70.7%. Factor that significantly associated with hand hygiene compliance was knowledge (p=0.001), while attitudes (p=0.577) and motivation (p=0.771) were not correlated significantly. Conclusion: Good knowledge increases the hand hygiene behavior among nurses in Class III inpatient wards of PKU Muhammadiyah Gamping Hospital. It is necessary to improve awareness through providing training on nurse compliance with the prevention and control of nosocomial infections, especially regarding proper steps and timing of hand hygiene practices.